CALCULATION OF OPERATING MODES OF CARDS TRANSFERS OF THE EXPERIMENTAL DIGGER FOR HARVESTING TOPINAMBUR (British Journal of Global Ecology and Sustainable Development, 2023)
The work of the cardan drive of a prototype digger for harvesting Jerusalem artichoke is characterized by a very difficult mode, large angles between the hinge shafts, which change during operation, dustiness and aggressiveness of the environment.